[Group portrait of football team in uniform] - Frank Aston::::::photographer::: (1916)
Group portrait of football team in uniform, with asst. coach CH.. Williams and coach D.W. Schlosser; on field, in line according to height; team members identified on back. Reversed image (see numbers on football). Photo of same team, seated on steps, was published in the Polytechnic J. (v.12, no.1, June 1917) with caption identifying members. Team members identified on back of postcard.